2016
DOI: 10.1111/eci.12695
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic chemerin mRNA expression is reduced in human nonalcoholic steatohepatitis

Abstract: Chemerin mRNA is reduced in the liver of NASH patients, and liver X receptor seems to have a role herein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 50 publications
1
36
1
2
Order By: Relevance
“…This result highlights a possible anti-inflammatory role for chemerin. In this context, Pohl et al (2017) found a downregulation of the chemerin mRNA levels in livers of humans suffering from a progressive form of NAFLD compared to humans suffering from steatosis alone.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This result highlights a possible anti-inflammatory role for chemerin. In this context, Pohl et al (2017) found a downregulation of the chemerin mRNA levels in livers of humans suffering from a progressive form of NAFLD compared to humans suffering from steatosis alone.…”
Section: Discussionmentioning
confidence: 92%
“…Chemerin has been identified as an adipokine in mouse, rat and human adipocytes (Bozaoglu et al, 2007;Goralski et al, 2007) and has a regulatory role in adipogenesis and adipocyte metabolism (Goralski et al, 2007). In addition to adipose tissue, chemerin is expressed in the liver as well (Pohl et al, 2017). Although substantial experimental evidence supports a proinflammatory role for chemerin (Weigert et al, 2010;Chakaroun et al, 2012;Döcke et al, 2013), other studies have suggested that chemerin might have anti-inflammatory properties (Cash et al, 2008;Luangsay et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We expect the AF-GGT relationship to be nullified when adjustment is made for oxidative stress, discouraging the use of GGT (or any liver enzymes) as markers of atrial fibrillation. Other n = 1 1 Chemerin mRNA is reduced in the liver of nonalcoholic fatty liver disease patients, and liver X receptor seems to have a role herein. Resistance to initial antibiotic treatment was associated with increased mortality.…”
Section: Directly Involved In Atrial Fibrillation: a Prospective Cohomentioning
confidence: 85%
“…Etiology of liver cirrhosis was alcoholic in 35, hepatitis C infection in three, and other reasons in three patients. Controls were randomly selected from a cohort of patients referred for ultrasound examination of the abdomen and patients without fatty liver (20). The study was approved by the local Ethical Committee of the University Hospital of Regensburg (approval number 15-101-0318) and written informed patient consent was obtained.…”
Section: Methodsmentioning
confidence: 99%